Law No. 19 of the Year 2023 On Legalizing the Conditions of Unlicensed Industrial Institutions = قانون رقم 19 لسنة 2023 بشأن تقنين أوضاع المنشآت الصناعية غير المرخص لها - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic